Karangsalam Village Towards Halal Rural Tourism: Evaluation and Prospects - Abdul Aziz Ahmad; Bambang Bambang; Sofiatul Khotimah (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2022)
The purpose of this study was to evaluate the condition of the Karangsalam rural tourism from the perspective of halal tourism concept and analyze the prospects for the development of the Karangsalam Village into a Halal Rural Tourism destination. To answer these objectives, this study uses descriptive qualitative analysis and SWOT Analysis. The findings of this study indicate that Karangsalam Village has tourist facilities, products and services that are friendly to Muslim tourists. The results of the SWOT analysis show greater strengths than weaknesses, and greater opportunities than threats. This means that Karangsalam Rural Tourism is very prospective to be developed into a Halal Rural Tourism destination. To advance the potential of halal tourism in Karangsalam Village, the local village government needs to contribute through the distribution of village fund allocations and community empowerment programs. Restaurant entrepreneurs also carry out halal certification to convince Muslim tourists.Keywords: rural tourism, halal tourism, karangsalam